3=−(−y+6)
Simplify:
3=−(−y+6)
3=y+−6(Distribute)
3=y−6
Flip the equation.
y−6=3
Add 6 to both sides.
y−6+6=3+6
y=9
Answer:
Step-by-step explanation:
Good evening ,
I guess it’s the C expression,
Because, C. 3n^2+n-2 so the coefficient of the term n is 1 and the coefficient of the term n^2 is 3
:)
Alright finding the mean of the set is pretty simple,
first add all the numbers that you were given.
0+2+3+4+6+6+7 add these up
28 then you need to divide them by
you divide by 7 because that's how many numbers you have
28 divided by 7 equals 4
so Sandy is correct.
Answer:
uh
Step-by-step explanation: